2018
DOI: 10.3389/fvets.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Mycobacterium avium subsp. hominissuis of Two Groups of Lymph Nodes, Being Intradermal Tuberculin or Interferon-Gamma Test Positive and Negative, Isolated from Swiss Cattle at Slaughter

Abstract: Mycobacterium avium subsp. hominissuis (MAH) is an important zoonotic pathogen with raising global health concerns. In humans, MAH is one of the most widespread non-tuberculous mycobacterial species responsible for lung disease. In animals, MAH is frequently isolated from pigs; however, it is also an opportunistic pathogen for other mammals including cattle. To elucidate the genetic diversity of MAH in cattle, a molecular characterization of isolates (n = 26) derived from lymph nodes was performed. Fourteen is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In the previous study of the relationship between the M. avium subsp. hominissuis (MAH) genotype and geographic origin, MAH from Japan seemed to be more closely related to the Korean lineage than Europe or the United States [ 23 , 29 ]. However, for M. intracellulare , there is still no reported relationship between geographic origin and genetic characteristics [ 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study of the relationship between the M. avium subsp. hominissuis (MAH) genotype and geographic origin, MAH from Japan seemed to be more closely related to the Korean lineage than Europe or the United States [ 23 , 29 ]. However, for M. intracellulare , there is still no reported relationship between geographic origin and genetic characteristics [ 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between animal and human isolates was also investigated. In the VNTR genotyping analysis using MATR and MIRU loci, some MAH Swiss isolates from bovine lymph nodes were similar to the pulmonary patient isolates from Netherlands, United States, and Japan [87]. The ISMav6 gene, which is distributed predominantly among isolates obtained from a patient in East Asian regions, was first found in isolates obtained from animals, indicating a close genetic association between the human and animal strains [87].…”
Section: Geographical Relationship Between Bacterial Strains Belonginmentioning
confidence: 82%
“…In the VNTR genotyping analysis using MATR and MIRU loci, some MAH Swiss isolates from bovine lymph nodes were similar to the pulmonary patient isolates from Netherlands, United States, and Japan [87]. The ISMav6 gene, which is distributed predominantly among isolates obtained from a patient in East Asian regions, was first found in isolates obtained from animals, indicating a close genetic association between the human and animal strains [87]. Additionally, a comparison of VNTR types analyzed using MIRU and MATR loci in previous studies of MANT BVLA01 strains isolated from cattle showed a close relationship between isolates obtained from Japanese patients and from the bathtub [88].…”
Section: Geographical Relationship Between Bacterial Strains Belonginmentioning
confidence: 83%
“…The tissue changes caused by MAC bacteria in cattle are indistinguishable from those caused by MTC bacteria, which may make diagnosis difficult. Granulomatous lesions are mainly located in the lymph nodes of the gastrointestinal and respiratory systems, although there have been cases of systemic disease [57,70,71]. Ruminants are most often infected by MAP, resulting in chronic inflammation of the intestines, called Johne's disease or paratuberculosis.…”
Section: Pathogenesis and Immunology Of Infection The Exact Pathogenesis Of Mac Infections And Their Virulence Factorsmentioning
confidence: 99%